Arabic Language Learning Management by Native Speaker - Bani, Moh. Yusuf; Sastradiharja, EE Junaedi; Farizal, Farizal; Toni, Toni; Riezqulloh, Anas (Al Irsyad: Jurnal Studi Islam, 2024)
TYou would like me to reduce this passage to zero words, meaning removing all the content. Could you confirm if that is your request or if you would like a different type of assistance with it? This research aims to analyze and describe the management of Arabic language learning by Native Speaker teachers in improving the learning outcomes of students at Mahad Al Wafi Islamic Boarding School. The research method used is qualitative, using a case study. Data collection techniques include interviews, observations, and documentation. Data processing involves reduction, presentation, and concluding. Research results: The planning of Arabic language learning involves steps to achieve the objectives, including selecting methods, media, and resources, with two models: collaborative and independent. An organization includes selecting materials aligned with the curriculum, applying appropriate teaching methods, and utilizing relevant media. Implementation combines a holistic approach with the boarding school model, using Student-Centered and Teacher-Centered Learning methods and practical exercises to enhance language skills and learning motivation. Learning supervision is carried out by both internal and external parties to ensure alignment with the plan and exam materials. Conclusion: The management of learning is well-structured, ensuring that each learning process runs effectively to achieve optimal educational goals.